Risk factors for urinary incontinence among Istanbul women: a hospital based case-control study - Nezihe Kizilkaya Beji; İlkay Güngör; Güliz Onat; Habibe Ayyildiz Erkan; Şule Gökyildiz; Önay Yalçin (University of Ostrava, 2018)
Aim: The study aimed to identify risk factors for urinary incontinence in women over 20 years of age in Istanbul. Design: The study was designed as a descriptive, retrospective, case control study. Methods: The study was conducted in a urogynecological unit at a university hospital in Istanbul. In total, 367 incontinent women who visited the urogynecological unit, and 401 continent women who visited outpatient clinics with other gynecological symptoms were included. Data were gathered via face-to-face interviews, using a questionnaire on risk factors for urinary incontinence. Adjusted odds ratios were given using logistic regression. Results: Variables which were found to be significantly different in chi-square analysis for urinary incontinence were age, education, marital status, number of pregnancies, birth and curettage, characteristics of first vaginal delivery (delivery mode, place, interventions), menopause, hormone therapy, history of gynecological operation, pulmonary disease, diabetes mellitus, hypertension, medicine use, constipation, flatus, hemorrhoids, herniated disc/varicose veins, stria during pregnancy, caffeine > 2 cups/day, body mass index (BMI ≥ 25 kg/m2), weight gain ≥ 10 kg, fecal incontinence, and history of urinary incontinence in childhood, in patients' mothers and relatives. When these variables were assessed in multivariate logistic regression analysis, number of births ("1-birth" OR = 38.8; CI = 2.2-669.5; "2-births" OR = 20.1; CI = 1.2-327.4; "≥ 3-births" OR = 35.0; CI = 1.9-621.8), BMI ≥ 25 kg/m2 (OR = 7.2; CI = 2.1-24.1), and history of incontinence in mothers (OR = 7.2; CI = 1.3-37.2) were identified as significant risk factors. Conclusion: The main risk factors for urinary incontinence in the population under study were identified to be the number of births as an obstetric risk factor, obesity as a lifestyle factor, and 'incontinence in mothers' as a familial factor. Keywords: pelvic floor, pelvic floor dysfunction, risk factors, urinary incontinence, urogynecology.